Funding behaviour of debt management offices and the ECB's Public Sector Purchase Programme - Katharina Plessen-Mátyás; Christoph Kaufmann; Julian von Landesberger (European Central Bank (ECB), 2021)
This paper investigates whether the funding behaviour of euro area debt management offices (DMOs) changed with the start of the ECB's Public Sector Purchase Programme (PSPP). Our results show that (i) lower yield levels and (ii) PSPP purchases supported higher maturities at issuance. The former indicates a behaviour of "locking in low rates for longer", while the latter suggests the existence of an additional "demand effect" of the PSPP on DMO strategies beyond the PSPP's effect via yields. The combined impact of the PSPP via these channels amounts to maturity extensions at issuance of about one year in our estimation, which compares to the average issuance maturity for Germany, France, Italy and Spain before the PSPP of four years. Our finding that DMOs extend maturities when funding conditions ease invites further work on the economic implications of public debt management during the PSPP and its relevance for monetary policy transmission.
Keywords: E52; E58; E63; H63; 330; Central bank asset purchases; unconventional monetary policy; public debtmanagement; sovereign debt maturity structure